2016
DOI: 10.1111/rda.12795
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation‐inducing factor (OIF/NGF) in seminal plasma: a review and update

Abstract: ContentsThe ovulation-inducing effect of seminal plasma was first reported in Bactrian camels over 30 years ago, and the entity responsible was dubbed 'ovulation-inducing factor' (OIF). More recent studies, primarily in llamas and alpacas, characterized the biological and chemical properties of OIF and ultimately identified it as βNGF. This recent discovery has allowed a convergence of knowledge previously separated by discipline and by mechanism; that is, neurobiology and reproductive biology, and autocrine/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 93 publications
1
37
0
2
Order By: Relevance
“…Furthermore, SP of SACs is also biochemically unique. An ovulation‐inducing protein factor (NGF‐ß) has been described (Adams, Ratto, Silva, & Carrasco, ), that not only induces ovulation by stimulating pituitary LH secretion but also adheres to the sperm membrane (Sari et al, ). On the other hand, a llama seminal lectin (SL15) that is likely adsorbed to spermatozoa via SP during ejaculation and is probably involved in sperm reservoir formation (Zampini, Sequeria, Argañaraz, & Apichela, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SP of SACs is also biochemically unique. An ovulation‐inducing protein factor (NGF‐ß) has been described (Adams, Ratto, Silva, & Carrasco, ), that not only induces ovulation by stimulating pituitary LH secretion but also adheres to the sperm membrane (Sari et al, ). On the other hand, a llama seminal lectin (SL15) that is likely adsorbed to spermatozoa via SP during ejaculation and is probably involved in sperm reservoir formation (Zampini, Sequeria, Argañaraz, & Apichela, ).…”
Section: Introductionmentioning
confidence: 99%
“…In llama also, Adams et al (36) reported that β-NGF and TrkA are present in the hypothalamus. Other studies have provided indirect evidences for the involvement of hypothalamus in the β-NGF-induced LH release.…”
Section: Identification Of the β-Ngf Central Target(s): The Kp Neuronmentioning
confidence: 99%
“…China's Bactrian camels are mainly distributed in Xinjiang, Inner Mongolia, Qinghai and Gansu; however in recent decades, camel populations have sharply declined (China Statistical Yearbook‐2016). One reason for this decline is the low reproductive efficiency of camels; they have a long reproductive cycle that progresses slowly although there is a similarity to GnRH/LH inducing factor of β‐NGF, which induce ovulation in female llamas and alpacas (Adams, Ratto, Silva, & Carrasco, ; Berland et al, ; Ratto et al, ). However, male Bactrian camel oestrous mechanism is unknown.…”
Section: Introductionmentioning
confidence: 99%